Evaluasi Proses Bisnis Pada PT Merdeka Grafika Indonesia Menggunakan Failure Mode and Effect Analysis (FMEA) dan Quality Evaluation Framework (QEF) - Rusjda Widya Rahmani; Aditya Rachmadi; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT Merdeka Grafika Indonesia is manufaturing company focusing in processing raw materials into good, known as producing. This company is specialized in printing and receives orders to print posters, newspapers, magazines, calenders, and tabloids. The process itself comprises of pre-printing, printing producing, dan finishing process. During the long duration of producing, many obstacles and failures is to be faced by this company. Obstacles and product fail happened because of defining custumer needs is not effective, machine downtime and data differences occur in stock information. All these times, the company is only focused to recreate a better version to any failure products and unaware enough to understand any failure in the producing activities. Because of that, evaluation considering the current unning business process needs to be conducted using the Failure Mode and Effect Analysis (FMEA) and Quality Evaluation Framework (QEF). The FMEA is usually helpful in order to understand any failures in the producing activity. On the other hands, the QEF is specifically a mean to understand any gaps between the targets and QEF calculations in the current company position. Both results are then multiplied, then searches to find the stem of the problem are conducted to figure out the cause of the root of the problem.